Analisis Nilai-Nilai Pendidikan Karakter Pada Film Animasi Riko The Series - Afina Asyya; Suparno (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study was to determine the value of character education in the animated film Riko The Series season 2 episodes 6 to 10. The data were obtained from observations of the film's dialogue script (primary) and articles related to the film (secondary). Based on the observation of the data, the researcher concludes that there are 6 values ​​of character education obtained. The value of character education obtained is the value of trust, religious value, caring value, unyielding value, curiosity, responsibility value.